PLANNING AND EVALUATION OF BIOEQUIVALENCE STUDIES OF ATAZANAVIR PRODUCTS - N. E. Uvarova; N. N. Eremenko; G. V. Ramenskaya; D. V. Goryachev (Регуляторные исследования и экспертиза лекарственных средств, 2018)
The Government of the Russian Federation approved the State strategy of combating the spread of HIV aimed at prevention of HIV epidemic. One of the goals of the Strategy is to increase the coverage of antiretroviral therapy for people infected with HIV, which includes extensive use of generic drugs. In order for a generic drug to be authorised, the applicant has to submit a report on the results of the bioequivalence studies in which the generic product was compared to the reference product. Atazanavir is an antiretroviral drug, which is also the drug of choice for the treatment and prevention of mother-to-child transmission of HIV. The aim of this study was to analyze the protocols and reports of atazanavir products bioequivalence studies, which were submitted for expert examination  to the FSBI “SCEEMP” of the Ministry of Health of the Russian Federation, and to prepare recommendations  for planning of bioequivalence studies of atazanavir products. The analysis of a number of studies revealed significant differences in the study design and number of subjects. The main reason for these differences is the conflicting data on the intrasubject coefficient of variation of atazanavir, which means that atazanavir may be considered a highly variable drug. The analysis helped to formulate  recommendations for the design of bioequivalence  studies of atazanavir products,  including studies of the maximum dose, studies under fed conditions, and consideration  of atazanavir variation when planning the study design.